Magnitude, composition and spatiotemporal patterns of vertebrate roadkill at regional scales: a study in southern Spain - Canal Piña, David (2018)
Although roadkill studies on a large scale are challenging, they can provide valuable information to assess the impact of road traffic on animal populations. Over 22 months (between July 2009–June 2010, and April 2011–March 2012) we surveyed 45 road sections of 10 km within a global biodiversity hotspot in Andalusia (87,000 km2), in southern Spain. We divided the region into five ecoregions differing in environmental conditions and landscape characteristics and recorded the relative magnitude, composition and spatiotemporal patterns of vertebrate (birds, mammal, amphibians, and reptiles) mortality. We used roadkill data from monthly surveys of road stretches with different speed limits, traffic volume, road design, and adjacent landscape composition. Roadkills varied over time and were not randomly distributed across ecoregions and road types. Overall, the groups most frequently encountered were mammals (54.4% of total roadkills) and birds (36.2%). Mortality rates in these two groups were higher on highways than on national or local roads, whereas those of amphibians (4.6%) and reptiles (4.3%) did not differ between road types. Except for mammals, the observed variation in vertebrate roadkills across ecoregions reflects the patterns of species richness previously described in the literature. Roadkills were concentrated over relatively short periods and this pattern was repeated over study periods and for all vertebrate classes. Our findings provide baseline information about road types, time periods and taxa with a higher probability of roadkills across an extensive region. These data represent an essential step towards the future implementation of broad–scale mitigation measures.